DAMPAK VIRUS CORONA TERHADAP SEKTOR PERDAGANGAN DAN SEKTOR PARIWISATA DI INDONESIA - Rinaldo Simbolon (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
Abstract Today the world is shocked by the spread of the corona outbreak virus that originated in China. As a result ofthis virus, many residents of China and many other countries have died. The Chinese economy has fallen fromcompanies that have to close. Given that China is the country with the largest economy in the world andIndonesia's main trading partner, the disruption of the Chinese economy will affect the world economyincluding Indonesia. This paper examines the impact of viruses on Indonesia's growth. The most dominantimpact occurs on trade. During January 2020, there was a drastic reduction in exports of imports from and toChina. Related to the efforts that can be made to overcome them, among other diversifications, export exportsto other countries; increase domestic production and consumption; and increasing domestic and foreigntourists.